Analisis Personal Branding Instagram Co-Founder Brand Pakaian Wanita Love, Bonito (Studi Instagram Rachel Lim @ms_rach) - Dennysal, Selena (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study examines how Rachel Lim, the co-founder of the women’s fashion brand Love, Bonito, strategically builds her personal branding through her Instagram account @ms_rach. The main issue addressed in this research is the growing significance of social media, particularly Instagram, in shaping personal identity and influencing brand perception. The objective is to analyze Rachel Lim’s personal branding strategies using Peter Montoya’s eight principles of personal branding. This research employed a qualitative descriptive method with a constructivist paradigm. Data were collected through direct observation of Instagram activities, in-depth interviews with Rachel Lim and selected followers, and supporting documentation. Thematic analysis was applied by categorizing content according to Montoya’s framework: specialization, leadership, personality, distinctiveness, visibility, unity, persistence, and goodwill. The findings reveal that Rachel Lim’s Instagram content consistently reflects the elements of effective personal branding. Her posts not only highlight her professional role but also integrate personal values, such as authenticity, empowerment, and family balance. These elements reinforce her identity as both a brand leader and a relatable figure. Her ability to combine her business vision with inspirational content strengthens the alignment between her personal brand and the mission of Love, Bonito. The study concludes that Rachel Lim has successfully utilized Instagram as a powerful platform to build a consistent and influential personal brand.